Casablanca [videorecording (DVD)] - Curtiz, Michael, 1886-1962; Bogart, Humphrey, 1899-1957; Bergman, Ingrid, 1915-1982; Henreid, Paul; Burnett, Murray (Turner Entertainment : distributed by Warner Home Video, 2012)
The romantic lovers' triangle between the impossibly heroic Czech Resistance leader Victor Laszlo, his beautiful wife Ilsa and her ex-lover, cynical American Rick Blaine is still the same old story, but it's never looked better.